A recyclable metal–organic framework for ammonia vapour adsorption. Issue 67 (22nd July 2020) - Nguyen, Tu N.; Harreschou, Ian M.; Lee, Jung-Hoon; Stylianou, Kyriakos C.; Stephan, Douglas W.
Abstract : The incorporation of sterically hindered boron centers into MOFs allows the recyclable adsorption of NH3 vapour from aqueous solution. Abstract : Herein, we present a new strategy to design metal–organic frameworks (MOFs) as adsorbents for ammonia (NH3 ) vapour. The linking ligand is functionalized with a sterically hindered Lewis acidic boron (B) centre, allowing efficient capture of NH3 and easy recycling of the MOF by simply heating at low temperature. The recycled MOF material can be used for NH3 capture for at least 5 cycles without losing its crystallinity or its luminescence properties.